Determination of Welfare Effect of Adaptation Policy for Rice Price Variation under Climate Change in Bangladesh - M. A. Salam; Jun Furuya; Shintaro Kobayashi (Emerging Challenges in Agriculture and Food Science Vol. 3, 2022)
This study was designed to evaluate the welfare effect of the climate adaptation policy for rice price variation in terms of producer surplus, consumer surplus, and net change in social welfare in Bangladesh, using the partial equilibrium model of the adaptation policy. The long-term trend of climate and policy adaptation for climate impact on price variation of the rice in Bangladesh is taken into economic model approach. The base period of this research is 1977-2009 and the extrapolation period is 2010-2030. To execute the designed analysis, the time series data from national and international organization are used. The results for the support price policy show that the total surplus that producers receive is equivalent to USD 1,164 million, substantially higher than the consumer surplus (USD 763 million) during the period 2010–2030. The net change in the social welfare owing to the support price policy is equivalent to –1483 million (USD) during the period 2010–2030. Moreover, analysis of the subsidized price policy shows that the total surplus that consumers receive (USD 1,958 million) is relatively higher than the producer surplus (USD 1,738 million) in the same period. The net change in social welfare owing to the subsidized price policy (–197 million USD) is much higher than that owing to price support –1483 million (USD). Implementing the dual price policy would result in a much higher net change in the society’s welfare (–1185 million USD) compared to that possible through each policy separately. In conclusion, these adaptation and price stabilization policies are recognized to be more useful in mitigating the severe price rise and fall in the future food market, in favour of both producers and consumers. Even though the change in net social welfare is higher, the higher cost of policy budget is imperative to make stable food supply and security.